Modul Pembelajaran Inkuiri Terbimbing Pada Materi Larutan Elektrolit dan Non Elektrolit - Siregar, Tiurlina; Natalia, Desry (Jurnal Ilmu Pendidikan Indonesia, 2019)
This study discusses the learning of guided inquiry learning models on the learning outcomes of chemicals in electrolyte and non-electrolyte solutions; (2) Improving learning outcomes of students after learning to use a guided inquiry learning model. The design of this study was quasi-experimental with the design of the One-Group-Pretest-Postest. The results showed: (1) there was a significant effect between guided incuition learning models on chemicals in electrolyte and non-electrolyte solutions with a significant value of 0.00 <0.05 (2) related to the results of chemical studies on electrolyte and non-electrolyte materials with n-Gain values averaging 0.72 high categories.